1999
DOI: 10.1073/pnas.96.4.1547
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent structure of an αβT cell receptor

Abstract: Whether there is one or multiple ␣␤T cell antigen receptor (TCR) recognition modules in a given TCR͞ CD3 complex is a long-standing controversy in immunology. We show that T cells from transgenic mice that coexpress comparable amounts of two distinct TCR␤ chains incorporate at least two ␣␤TCRs in a single TCR͞CD3 complex. Evidence for bispecific ␣␤TCRs was obtained by immunoprecipitation and immunoblotting and confirmed on the surface of living cells both by f luorescence resonance energy transfer and comodula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 55 publications
3
98
0
Order By: Relevance
“…Thus, the overall stoichiometry of the TCR complex was found to be 1:1:1:1:2:2 (for TCR, TCR, CD3 , CD3 , CD3 , and CD3 , respectively) (Rudolph et al, 2006;Wucherpfennig et al, 2010) These findings corroborated the stoichiometry proposed in a previous study (Blumberg et al, 1990), and are supported by other results, as well (Call et al, 2004). However, other works suggested that a second heterodimer was incorporated into the complex, suggesting an ( ) 2 stoichiometry (Exley et al, 1995;Fernandez-Miguel et al, 1999;San Jose et al, 1998). Finally, an ( ) 2 configuration was also suggested (Rubin et al, 2002).…”
Section: Current Understanding Of Stoichiometry Of the Complexes Invosupporting
confidence: 82%
“…Thus, the overall stoichiometry of the TCR complex was found to be 1:1:1:1:2:2 (for TCR, TCR, CD3 , CD3 , CD3 , and CD3 , respectively) (Rudolph et al, 2006;Wucherpfennig et al, 2010) These findings corroborated the stoichiometry proposed in a previous study (Blumberg et al, 1990), and are supported by other results, as well (Call et al, 2004). However, other works suggested that a second heterodimer was incorporated into the complex, suggesting an ( ) 2 stoichiometry (Exley et al, 1995;Fernandez-Miguel et al, 1999;San Jose et al, 1998). Finally, an ( ) 2 configuration was also suggested (Rubin et al, 2002).…”
Section: Current Understanding Of Stoichiometry Of the Complexes Invosupporting
confidence: 82%
“…Our model of the αβTCR-CD3 complex, with CD3δε and CD3γε clustered on one side of the TCR (7), stands in contrast to those in which the CD3 heterodimers dock on opposite sides of the TCR (21) or in which two TCRs are associated with one set of signaling dimers (16). To discriminate between these models, we used a dimerization reporter system based on the knowledge that erythropoietin receptor (EPOR) signaling, via the Jak-Stat pathway when two signaling domains are in juxtaposition (22), can drive BaF3 cell proliferation (23).…”
Section: Resultsmentioning
confidence: 99%
“…Residues that stabilize TCR-CD3 interactions have been implicated in signaling (6,7,9) and subtle conformational changes have been proposed (10). In addition, dimerization of the complex is thought to be important because forcing TCRs into juxtaposition can induce signaling (11,12); however, the evidence for dimerization has been controversial (13)(14)(15)(16), and the structural features that would mediate such interactions have not been identified. A more complete understanding of how the subunits fit together within and between complexes is needed to advance our understanding of how this molecular machinery works.…”
mentioning
confidence: 99%
“…Indeed, TCR:28ε-mediated, but not wt TCR-mediated, immune synapses were readily detectable in primary human T cells, showed enhanced accumulation of TCR, CD3, and CD8 (Figs. 5, 6), and are expected to facilitate Ag-dependent T cell activation (44,46,47). Notably, TCR:z mediates immune synapses in which densities of TCR, CD3, and CD8 are diluted over enlarged contact areas (23), whereas TCR:28ε mediates immune synapses in which densities of the aforementioned molecules are enriched in normal-sized immune synapses.…”
Section: Discussionmentioning
confidence: 99%